Influence of Free Radicals in the Origin of Atherosclerosis - Yoel Hernández Guerra; Alain Rodríguez Gómez; Janet Villafuerte Reinante; Ignacio Marrero Silva; Carlos Manuel Mora Hernández (Revista Finlay)
Most of the pathologic components of oxidative stress of cardiovascular diseases are closely related with diregulation of metabolism of reactive species of oxygen, which favor the appearance of the so called oxidative stress. The oxidation of low density lipoproteins, endothelial dysfunction and inflammatory processes are mediated in some way by cellular production of the reactive oxygen species. This review is conducted aimed at revising the latest findings that explain the influence of free radicals in the origin of atherosclerosis. It is concluded that oxygen is the main source of free radical formation whose action is determinant for the genesis of atherosclerosis. The increase of oxidative stress favors atherothrombatic phases: platelet adhesion and aggregation, cell proliferation, lipid and protein perioxidation, irreversible damage in DNA and mitochondrial membrane and inestabilzation/desestabilization of the plaque.